Formulation of ice cream based on pulp of tamarind (Tamarindus indica L.) with hydrocoloids and enriched with vitamin C - Bravo Aranibar, Juan Carlos (2019)
This research is based on the need to develop a new production line for fruit ice cream. Currently, tamarind in the national market can be found in products such as marcianos, cremoladas, ingredients in the kitchen, jellies or as fruit. The proposal of the work is innovative, since it raises the possibility of taking advantage of the pulp of the fruit in ice cream as an industrial input, due to the high concentration of tartaric acid found in the pulp. For ice cream, hydrocolloids (guar gum and xanthan gum) are used to provide a typical texture of fruit ice cream with milk, in addition to being enriched with ascorbic acid as a source of vitamin C. Three ice cream formulations were made that in its last stage mixing and freezing processes were assembled at an industrial artisanal ice cream plant to have better sensory characteristics. Ice creams were tasted and evaluated by means of a survey to determine the level of acceptance by means of questions with hedonic scale measurement in relation to color, flavor, texture and general appearance. In the perception of the respondents, the reaction of the sensation of the new flavor of tartaric acid of tamarind was observed, which, in combination with ascorbic acid, lactic acid of milk further highlighted the acidity of the ice cream and the hydrocolloids used that gave them the Typical texture of an ice cream. Finally, the use of in different proportions of guar and xanthan gums determined that the third formulation with code 190 obtained the highest level of acceptability.